PENERAPAN TARGET COSTING DALAM UPAYA MENINGKATKAN EFISISENSI BIAYA PRODUKSI - Manalu, Elita Tia Monica; Hia, Resi Restu; Saribu, Ardin Dolok; Zega, Nopitri; Sijabat, Juni Debora; Nainggolan, Jestri Sumerdi; Simatupang, Mula (Komunitas Manajemen Kompetitif, 2025)
The main objective of this critical journal is to analyze the advantages and disadvantages of the main journal articles in the application of target costing in an effort to improve production cost efficiency. This study uses a target costing approach which is expected to be an effective production cost control tool. The research method used is the literature study method. The main journal used is